Physiological response of sweet corn (Zea mays var. merit) to foliar application of salicylic acid under water deficit stress (Bangladesh Journal of Botany, 2018)
The effect of water deficit stress and salicylic acid application on physiological characteristics of sweet corn (Zea mays var. Merit), an experiment was conducted. Treatments were water deficit stress in three levels: a1: normal irrigation (100% FC irrigation), a2: fair stress (75% FC irrigation) and a3: mild stress (50% FC irrigation). The second factor was the 0/1 mM salicylic acid application in six levels [b1: control, b2: seed priming, b3: SA application in 3 leaves stage, b4: SA application in pollination stage, b5: seed priming + SA application in pollination stage and b6: SA application at 3 leaves stage + pollination stage. The analysis of variance showed significant effect of interaction between water deficit stress and SA application on Chl. a, Chl. b, Chl. a + b, 100-grain weight and ear yield (p < 0.01). Results showed that SA application at 3-leaves stage + pollination stage indicated five times more Chl.a as compared with control in 50% FC irrigation. SA application at 3-leaves stage proved 4/2 and 4/4 times more Chl.b and Chl. a + b as compared to control in mild stress. SA application at pollination stage had the highest (36/15 g) and control at mild stress had the lowest (10/56 g) 100-grain weight. Also, SA application at 3-leaves stage + pollination stage had the highest (245/1 g/plant) and control at mild stress had the lowest (74/25 g/plant) ear yield.